Zirconium-doped high-nickel ternary precursor material as well as preparation method and application thereof
By using metaborate as a precipitant in the preparation of ternary precursor materials, the OH- is slowly provided, which solves the problems of uneven particle morphology and uneven particle size distribution, and significantly improves the compressive resistance and cycling performance of the material.
Patent Information
- Application Number
- CN202411903682.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
During the preparation process, existing ternary precursor materials have problems such as uneven particle morphology, poor compressive resistance, and uneven particle size distribution, which affects the circulation performance and stability of lithium-ion batteries.
Metaborate is used as the precipitant, and OH- is provided slowly through co-precipitation reaction, controlling the precipitation rate, reducing the generation of new crystal nuclei, and improving the sphericality and particle size distribution of particles.
The compressive resistance, stability and sphericality of the precursor material are significantly improved, the particle size distribution is optimized, and the circulation performance of lithium-ion batteries is enhanced.
Smart Images

Figure BDA0005203861460000121 
Figure BDA0005203861460000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a zirconium-doped high-nickel ternary precursor material and a preparation method and application thereof. Background Art
[0002] With the rapid development of the new energy industry, the application of electric vehicles and lithium-ion batteries is becoming more and more extensive. Lithium-ion batteries have attracted widespread attention and application due to their advantages such as high energy density, long cycle performance and no memory effect. The correct selection of positive electrode materials for lithium-ion batteries is an indispensable part of improving the performance of lithium-ion batteries, and the selection of precursors for preparing positive electrode materials cannot be ignored. Among the ternary precursor materials, especially metal oxides such as nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA), they are widely used in lithium-ion battery positive electrode materials. As the core of the next generation of high-energy-density lithium battery materials, their performance directly determines the cycle life, energy density and safety of the battery. In the preparation process of these ternary precursor materials, the particle morphology and particle size distribution will affect the final electrochemical performance.
[0003] For example, CN 111717940A discloses a method for preparing a narrow distribution precursor by grading, wherein the prepared seed crystals are screened in multiple stages by a screening device, and the screened particles with smaller particle sizes are returned to the seed crystal reactor to continue the reaction, while the particles with larger particle sizes exceeding the target range are removed to ensure the overall consistency of the seed crystals, thereby obtaining a ternary precursor with a narrow particle size distribution. This method makes the primary particles and secondary agglomerates on the surface of the product highly consistent, solving the problem of poor cycle performance of the current ternary cathode material due to uneven particle size distribution from the source, but this method has a complicated operation process and requires multiple screenings, which greatly increases the workload.
[0004] CN 116354412A discloses a method for preparing a doped ternary precursor for improving the sphericity of large particles, comprising the following steps: 1. preparing zirconium-doped crystal nuclei by adding zirconium oxide microsphere suspension to a nickel-cobalt-manganese mixed salt solution; 2. continuously adding the nickel-cobalt-manganese mixed salt solution, a precipitant, a complexing agent, a zirconium oxide microsphere suspension, and a crystal nucleus slurry into a reactor to prepare a ternary precursor slurry; 3. preparing a zirconium-doped ternary precursor. The doping preparation method is relatively complicated, and although the prepared precursor has a good sphericity, the particle size distribution is poor.
[0005] Therefore, the precursors prepared by the conventional seed crystal method have problems such as uneven structure and poor compressive resistance, which limits their stability and cycle life under high temperature conditions. In addition, sodium hydroxide is often used as a precipitant in the prior art, but the high alkaline environment it induces easily causes damage to the surface of the seed crystal. At the same time, during the growth of large-particle ternary precursors, the pH is regulated by sodium hydroxide. -The rapid release of large particles easily generates small particles during the growth of large particles, which leads to a wider particle size distribution and ultimately reduces the cycle performance of the battery.
[0006] Based on the above research, it is necessary to provide a method for preparing a high-nickel ternary precursor material. The precursor obtained by the preparation method not only has high compressive resistance and stability, but also has high sphericity and uniform particle size distribution. Summary of the invention
[0007] The purpose of the present invention is to provide a zirconium-doped high-nickel ternary precursor material and a preparation method and application thereof. The preparation method adopts metaborate as a precipitant to prepare a zirconium-doped high-nickel ternary precursor material, and at the same time constructs a seed and controls the subsequent OH - The slow release improves the compression resistance and stability of the precursor material, improves the sphericity and particle size distribution of the precursor material, and improves the cycle performance of lithium-ion batteries.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a zirconium-doped high-nickel ternary precursor material, the preparation method comprising the following steps:
[0010] (1) introducing a zirconium-doped mixed metal salt solution, a mixed coprecipitant solution and a complexing agent solution into a first base solution to perform a first coprecipitation reaction to obtain a seed solution, and removing the solvent in the seed solution to obtain seed crystals;
[0011] The mixed coprecipitant solution includes metaborate and hydroxide;
[0012] (2) After mixing the seed crystals described in step (1) with the second base liquid to obtain a second base liquid containing seed crystals, a zirconium-doped mixed metal salt solution, a metaborate solution and a complexing agent solution are introduced into the second base liquid containing seed crystals to perform a second coprecipitation reaction to obtain the zirconium-doped high-nickel ternary precursor material.
[0013] In the prior art, the coprecipitation method is the main method for preparing the ternary cathode precursor material, which is to use sodium hydroxide as a precipitant and ammonia as a complexing agent for coprecipitation preparation. - However, the hydrolysis of sodium hydroxide will still cause the formation of new crystal nuclei during the growth of large-particle precursors, thus affecting the particle size distribution. - The rapid release will affect the sphericity of the particles, causing the seed crystal to have a loose connection layer structure during the subsequent growth process, leading to faults during the subsequent sintering process.
[0014] The present invention uses metaborate as a precipitant to carry out a coprecipitation reaction, which can slowly provide OH - ; Specifically, metaborate will present various anionic forms when dissolved in water, and the main borate anion is B(OH)4 - , but there are other polyborates, such as B(OH)3, B3O3(OH)4 - and B4O5(OH)4 2- , and polyborate anions, the total concentration of these substances is less than 5%, among which the [BO4] group is tetrahedral in shape, which promotes the formation of polyborate rings, while the BO group bonds with the transition metal and polymerizes into an open framework structure with a large surface area, and at the same time Therefore, the present invention uses metaborate as a precipitant to slowly provide OH in the nucleation process. - , thereby controlling the precipitation rate, reducing the generation of new crystal nuclei during the growth of large particles, and avoiding faults in the subsequent sintering process.
[0015] In addition, in the nucleation stage of forming seed crystals in step (1), the precipitant used is a mixed precipitant of metaborate and hydroxide to promote the formation of seed crystals. After the seed crystals are obtained, only metaborate is used as a precipitant to gently perform a coprecipitation reaction to slowly release OH. - , to avoid the generation of small particles in the growth stage of the precursor particles. Therefore, the preparation method of the present invention can generate a precursor with excellent sphericity, narrow particle size distribution and uniform distribution of doping elements without obvious cracks, and can also significantly improve the problem of the precursor having an insufficiently tight connection layer structure due to the two-step method, and optimize the problem of easily generating new crystal nuclei during the growth of large-particle precursors. At the same time, this method can significantly reduce the occurrence of cracks in the material during the later calcination process, and can also optimize the grain boundaries and improve the cycle stability of the battery.
[0016] Preferably, in the mixed coprecipitant solution of step (1), the molar ratio of hydroxide to metaborate is (1.4-1.8):1, for example, it can be 1.4:1, 1.5:1, 1.6:1, 1.7:1 or 1.8:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] When preparing the seed crystal in step (1) of the present invention, the molar ratio of hydroxide to metaborate in the mixed coprecipitant solution will affect the OH - If the amount of metaborate is too much compared to hydroxide, less OH- will be released, and the growth rate of the precursor will be too slow. If the amount of metaborate is too little compared to hydroxide, it will lead to excessive and too fast nucleation, slow particle growth, and agglomeration may also occur.
[0018] Preferably, in the mixed coprecipitant solution of step (1), the concentration of hydroxide is 9-10 mol / L, for example, 9 mol / L, 9.25 mol / L, 9.5 mol / L, 9.75 mol / L or 10 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, in the mixed coprecipitant solution of step (1), the concentration of metaborate is 5.5-7 mol / L, for example, 5.5 mol / L, 6 mol / L, 6.5 mol / L or 7 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0020] Preferably, the hydroxide in step (1) comprises sodium hydroxide.
[0021] Preferably, the metaborate in step (1) comprises sodium metaborate.
[0022] Preferably, the particle size D50 of the seed crystal in step (1) is 3-4.5 μm, for example, 3 μm, 3.5 μm, 4.0 μm or 4.5 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Preferably, in the zirconium-doped mixed metal salt solution of step (1), the concentration of zirconium ions is 20-60 mmol / L, for example, 20 mmol / L, 30 mmol / L, 40 mmol / L, 50 mmol / L or 60 mmol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] Preferably, the zirconium salt of the zirconium-doped mixed metal salt solution includes any one of sulfate, nitrate or chloride, or a combination of at least two of them.
[0025] Preferably, in the zirconium-doped mixed metal salt solution of step (1), the molar ratio of nickel ions, cobalt ions and manganese ions is (0.9-0.98):(0.1-0.6):(0.1-0.2), for example, it can be 0.96:0.3:0.1, 0.90:0.6:0.2 or 0.98:0.1:0.1, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Preferably, the first base solution in step (1) comprises a complexing agent, a metaborate and a hydroxide.
[0027] Preferably, the pH of the first base solution in step (1) is 11-12, for example, 11, 11.5 or 12, the concentration of the complexing agent in the first base solution is 0.12-0.15 mol / L, for example, 0.12 mol / L, 0.13 mol / L, 0.14 mol / L or 0.15 mol / L, the concentration of the hydroxide is 0.3-0.38 mol / L, for example, 0.3 mol / L, 0.35 mol / L or 0.38 mol / L, and the concentration of the metaborate is 0.2-0.21 mol / L, for example, 0.2 mol / L, 0.205 mol / L or 0.21 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0028] Preferably, during the first coprecipitation reaction in step (1), the pH is 11-11.5, for example, 11.0, 11.2, 11.4 or 11.5, and the concentration of the complexing agent is 0.1-0.15 mol / L, for example, 0.1 mol / L, 0.12 mol / L, 0.14 mol / L or 0.15 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0029] Preferably, during the first coprecipitation reaction in step (1), the concentration of hydroxide is 1.8-2 mol / L, for example, 1.8 mol / L, 1.9 mol / L or 2 mol / L, and the concentration of metaborate is 1-1.4 mol / L, for example, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L or 1.4 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] The molar ratio of hydroxide to metaborate in the mixed coprecipitant solution of the present invention will affect the concentration of hydroxide and metaborate in the first coprecipitation reaction, thereby affecting the OH - release rate.
[0031] Preferably, during the second coprecipitation reaction in step (2), the concentration of the metaborate solution is 4-8 mol / L, for example, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L or 8 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In the present invention, when the particles are grown, the concentration of the metaborate solution is preferably 4-8 mol / L, which will affect the growth of the particles. If the concentration of the metaborate solution is too low, OH -The content decreases, resulting in finer primary particles. If the concentration of the metaborate solution is too high, the number of polyborate rings in the system will increase, reducing the coprecipitation rate.
[0033] Preferably, during the second coprecipitation reaction in step (2), the pH is 7.5-9, for example, 7.5, 8, 8.5 or 9, and the concentration of the complexing agent is 0.2-0.25 mol / L, for example, 0.2 mol / L, 0.22 mol / L, 0.24 mol / L or 0.25 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Preferably, the temperature of the coprecipitation reaction in step (1) and step (2) is 40-60°C, for example, 40°C, 50°C or 60°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] Preferably, the second base liquid in step (2) comprises a complexing agent and a metaborate.
[0036] Preferably, the pH of the second base solution in step (2) is 8-10, for example, 8, 9 or 10, the concentration of the complexing agent is 0.2-0.3 mol / L, for example, 0.2 mol / L, 0.25 mol / L or 0.3 mol / L, and the concentration of the metaborate is 6-8 mol / L, for example, 6 mol / L, 7 mol / L or 8 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0037] Preferably, the particle size D50 of the zirconium-doped high-nickel ternary precursor material in step (2) is 9-13 μm, for example, 9 μm, 10 μm, 11 μm, 12 μm or 13 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] The preparation method of the present invention is preferably aimed at large-particle precursor materials, and can solve the problem that large-particle precursors are prone to produce small particles during the preparation process.
[0039] Preferably, the PDI (Polydispersity Index, PDI, is one of the important parameters to characterize the uniformity of particle distribution. The smaller the value, the narrower the particle size distribution range) of the zirconium-doped high-nickel ternary precursor material in step (2) is 0.29-0.4, for example, it can be 0.29, 0.325, 0.35, 0.375 or 0.4, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0040] Preferably, the tap density of the zirconium-doped high-nickel ternary precursor material in step (2) is 1.98-2.1 g / cm 3 , for example, it can be 1.98 g / cm 3 , 1.99g / cm 3 , 2.0g / cm 3 or 2.1 g / cm 3 , with a specific surface area of 14.8-18m 2 / g, for example, it can be 14.8m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g or 18m 2 / g, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0041] In a second aspect, the present invention provides a zirconium-doped high-nickel ternary precursor material, wherein the zirconium-doped high-nickel ternary precursor material is prepared by the preparation method described in the first aspect.
[0042] In a third aspect, the present invention provides a high-nickel ternary positive electrode material, which is obtained by mixing and sintering a lithium source and a zirconium-doped high-nickel ternary precursor material as described in the second aspect.
[0043] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the high-nickel ternary positive electrode material as described in the third aspect.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] The present invention uses metaborate as a precipitant to gently regulate the reaction process OH - The release process can significantly improve the problem of insufficient tightness of the connection layer structure of the precursor caused by the two-step method, as well as the problem of uneven particle size distribution caused by the generation of new crystal nuclei and small particles during the growth of large-particle precursors. It can generate precursor materials with high sphericity, narrow particle size distribution and uniform distribution of doping elements without obvious cracks, and can also significantly reduce the cracks in the material during the later calcination process, optimize the grain boundaries, and improve the cycle stability of the battery. DETAILED DESCRIPTION
[0046] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0047] Example 1
[0048] This embodiment provides a method for preparing a zirconium-doped high-nickel ternary precursor material, the preparation method comprising the following steps:
[0049] (1) nickel salt, cobalt salt and manganese salt are prepared in a molar ratio of Ni:Co:Mn=0.96:0.3:0.1 to form a mixed salt solution with a total metal ion concentration of 1 mol / L, and the zirconium ion concentration doped in the mixed salt solution is 30 mmol / L;
[0050] A mixed coprecipitant solution is prepared, wherein the molar ratio of sodium hydroxide to sodium metaborate is 1.6:1 (the concentrations of sodium hydroxide and sodium metaborate are 9 mol / L and 5.5 mol / L, respectively);
[0051] (2) Volume is 1m 3 500L of water was added to the reactor, stirred at a speed of 420rpm, the temperature was controlled at 55°C, ammonia and mixed coprecipitant solution were added to prepare a base solution (the pH of the base solution was 11, the ammonia concentration was 0.15mol / L, and the concentrations of sodium hydroxide and sodium metaborate were 0.35mol / L and 0.21mol / L, respectively), and after stirring and mixing for 30min, the metering pumps of the mixed salt solution, ammonia water, and mixed coprecipitant solution were turned on to prepare seed crystals, wherein the pH of the seed crystal reaction stage was controlled at 11-11.5, the ammonia concentration was 0.15mol / L, the rotation speed was 420rpm, and the reaction was stopped when the particle size was 4μm;
[0052] (3) The seed crystals after centrifugal washing are placed in a second reaction kettle (the pH of the second bottom liquid in the second reaction kettle is 9, the ammonia concentration is 0.25 mol / L, and the concentration of sodium metaborate is 7 mol / L), and then a mixed salt solution, sodium metaborate solution and ammonia water are introduced into the second reaction kettle for reaction. The pH of the reaction process is controlled at 8.5-9, the ammonia concentration is controlled at 0.25 mol / L, the concentration of sodium metaborate is 6 mol / L, the rotation speed is 140 rpm, and washing is started after the reaction is stopped;
[0053] The particle size D50 of the precursor material prepared above is 9.32 μm, the particle size distribution PDI is 0.292, and the tap density is 2.1 g / cm 3 , with a specific surface area of 17.96m 2 / g.
[0054] Example 2
[0055] This embodiment provides a method for preparing a zirconium-doped high-nickel ternary precursor material, the preparation method comprising the following steps:
[0056] (1) nickel salt, cobalt salt and manganese salt are prepared in a molar ratio of Ni:Co:Mn=0.90:0.6:0.2 to form a mixed salt solution with a total metal ion concentration of 1 mol / L, and the zirconium ion concentration doped in the mixed salt solution is 20 mmol / L;
[0057] A mixed coprecipitant solution is prepared, wherein the molar ratio of sodium hydroxide to sodium metaborate is controlled at 1.4:1 (the concentrations of sodium hydroxide and sodium metaborate are 10 mol / L and 7.1 mol / L, respectively);
[0058] (2) Volume is 1m 3 500L of water was added to the reactor, stirred at a speed of 420rpm, the temperature was controlled at 55°C, ammonia and mixed coprecipitant solution were added to prepare a base solution (the pH of the base solution was 12, the ammonia concentration was 0.15mol / L, and the concentrations of sodium hydroxide and sodium metaborate were 0.38mol / L and 0.2mol / L, respectively), and after stirring and mixing for 30min, the metering pumps of the mixed salt solution, ammonia water, and mixed coprecipitant solution were turned on to prepare seed crystals, wherein the pH of the seed crystal reaction stage was controlled at 11, the ammonia concentration was 0.15mol / L, the rotation speed was 420rpm, and the reaction was stopped when the particle size was 4.5μm;
[0059] (3) The seed crystals after centrifugal washing are added into a second reactor for reaction (the pH of the second bottom liquid in the second reactor is 8, the ammonia concentration is 0.2 mol / L, and the concentration of sodium metaborate is 6 mol / L), and then a mixed salt solution, sodium metaborate solution and ammonia water are introduced into the second reactor for reaction. The pH of the reaction process is controlled at 7.5-8, the ammonia concentration is controlled at 0.2 mol / L, the concentration of sodium metaborate is 4 mol / L, the rotation speed is 140 rpm, and washing is started after the reaction is stopped;
[0060] The particle size D50 of the precursor material prepared above is 12.12 μm, the particle size distribution PDI is 0.398, and the tap density is 1.98 g / cm 3 , with a specific surface area of 15.22m 2 / g.
[0061] Example 3
[0062] This embodiment provides a method for preparing a zirconium-doped high-nickel ternary precursor material, the preparation method comprising the following steps:
[0063] (1) nickel salt, cobalt salt and manganese salt are prepared in a molar ratio of Ni:Co:Mn=0.98:0.1:0.1 to form a mixed salt solution with a total metal ion concentration of 1 mol / L, and the zirconium ion concentration doped in the mixed salt solution is 30 mmol / L;
[0064] A mixed coprecipitant solution is prepared, wherein the molar ratio of sodium hydroxide to sodium metaborate is 1.8:1 (the concentrations of sodium hydroxide and sodium metaborate are 10 mol / L and 5.5 mol / L, respectively);
[0065] (2) Volume is 1m 3 500L of water was added to the reactor, stirred at a speed of 420rpm, the temperature was controlled at 55°C, ammonia and mixed coprecipitant solution were added to prepare a base solution (the pH of the base solution was 11, the ammonia concentration was 0.12mol / L, and the concentrations of sodium hydroxide and sodium metaborate were 0.30mol / L and 0.21mol / L, respectively), and after stirring and mixing for 30min, the metering pumps of the mixed salt solution, ammonia water, and mixed coprecipitant solution were turned on to prepare seed crystals, wherein the pH of the seed crystal reaction stage was controlled at 11, the ammonia concentration was 0.15mol / L, the rotation speed was 420rpm, and the reaction was stopped when the particle size was 4μm;
[0066] (3) The seed crystals after centrifugal washing are added into a second reactor for reaction (the pH of the second bottom liquid in the second reactor is 10, the ammonia concentration is 0.3 mol / L, and the concentration of sodium metaborate is 8 mol / L), and then a mixed salt solution, sodium metaborate solution and ammonia water are introduced into the second reactor for reaction. The pH of the reaction process is controlled at 8.5-9, the ammonia concentration is controlled at 0.25 mol / L, the concentration of sodium metaborate is 8 mol / L, the rotation speed is 140 rpm, and washing is started after the reaction is stopped;
[0067] The particle size D50 of the precursor material prepared above is 13.09 μm, the particle size distribution PDI is 0.342, and the tap density is 2.01 g / cm 3 , with a specific surface area of 14.87m 2 / g.
[0068] Example 4
[0069] This embodiment provides a method for preparing a zirconium-doped high-nickel ternary precursor material. The preparation method is the same as that of Example 1, except that the molar ratio of sodium hydroxide to sodium metaborate in step (1) is controlled to be 2.2:1.
[0070] Example 5
[0071] This embodiment provides a method for preparing a zirconium-doped high-nickel ternary precursor material. The preparation method is the same as that of Embodiment 1, except that the molar ratio of sodium hydroxide to sodium metaborate in step (1) is controlled to be 1:1.
[0072] Example 6
[0073] This embodiment provides a method for preparing a zirconium-doped high-nickel ternary precursor material. The preparation method is the same as that of Embodiment 1, except that the concentration of sodium metaborate in step (3) is 2 mol / L.
[0074] Example 7
[0075] This embodiment provides a method for preparing a zirconium-doped high-nickel ternary precursor material. The preparation method is the same as that of Embodiment 1, except that the concentration of sodium metaborate in step (3) is 10 mol / L.
[0076] Comparative Example 1
[0077] This comparative example provides a method for preparing a zirconium-doped high-nickel ternary precursor material, which is the same as Example 1 except that the mixed coprecipitant solution in step (1) only includes sodium hydroxide and does not include sodium metaborate.
[0078] Comparative Example 2
[0079] This comparative example provides a method for preparing a zirconium-doped high-nickel ternary precursor material. The preparation method is the same as Example 1 except that the sodium metaborate solution in step (3) is replaced by a sodium hydroxide solution of equal concentration.
[0080] The particle size distribution PDI of the zirconium-doped high-nickel ternary precursor material obtained in the above examples and comparative examples is shown in Table 1.
[0081] The zirconium-doped high-nickel ternary precursor material obtained in the above examples and comparative examples was heated to 500°C with lithium hydroxide, kept warm for 7 hours, and then continued to be heated to 900°C for calcination for 20 hours to obtain a positive electrode material; the prepared positive electrode material, conductive carbon black and polyvinylidene fluoride were made into a positive electrode slurry in a mass ratio of 8:1:1, and the positive electrode slurry was coated on aluminum foil to make a positive electrode sheet, which was then assembled into a button battery with a lithium sheet polyethylene diaphragm and a lithium hexafluorophosphate electrolyte. The button battery was tested for 100 cycles of cycle performance at a temperature of 45°C and a voltage range of 2.7-4.5V. The test results are shown in Table 1:
[0082] Table 1
[0083]
[0084]
[0085] From the above table we can see that:
[0086] It can be seen from Example 1 and Comparative Examples 1-2 that in the present invention, when preparing seed crystals, metaborate and hydroxide are used as mixed precipitants, and metaborate is used as a precipitant during particle growth, which can slowly release OH- , avoiding the generation of new small particles during growth, and at the same time avoiding the problem of loose connection layer structure during two-step co-precipitation. Therefore, the PDI obtained by the present invention is small and the cycle performance is excellent. It can be seen from Examples 1 and 4-7 that the molar ratio of sodium hydroxide and sodium metaborate in step (1) of the present invention and the concentration of sodium metaborate in step (3) will affect the OH concentration during the co-precipitation process. - The release rate of the precursor material affects the performance of the obtained precursor material.
[0087] In summary, the present invention provides a zirconium-doped high-nickel ternary precursor material and a preparation method and application thereof. The preparation method uses metaborate as a precipitant to prepare a zirconium-doped high-nickel ternary precursor material, and at the same time constructs a seed crystal and controls the subsequent OH - The slow release improves the compression resistance and stability of the precursor material, improves the sphericity and particle size distribution of the precursor material, and improves the cycle performance of lithium-ion batteries.
[0088] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a zirconium-doped high-nickel ternary precursor material, characterized in that: The preparation method comprises the following steps: (1) introducing a zirconium-doped mixed metal salt solution, a mixed coprecipitant solution and a complexing agent solution into a first base solution to perform a first coprecipitation reaction to obtain a seed solution, and removing the solvent in the seed solution to obtain seed crystals; The mixed coprecipitant solution includes metaborate and hydroxide; (2) After mixing the seed crystals described in step (1) with the second base liquid to obtain a second base liquid containing seed crystals, a zirconium-doped mixed metal salt solution, a metaborate solution and a complexing agent solution are introduced into the second base liquid containing seed crystals to perform a second coprecipitation reaction to obtain the zirconium-doped high-nickel ternary precursor material.
2. The preparation method according to claim 1, characterized in that: In the mixed coprecipitant solution of step (1), the molar ratio of hydroxide to metaborate is (1.4-1.8):1; Preferably, in the mixed coprecipitant solution of step (1), the concentration of hydroxide is 9-10 mol / L; Preferably, in the mixed coprecipitant solution of step (1), the concentration of metaborate is 5.5-7 mol / L; Preferably, the hydroxide in step (1) comprises sodium hydroxide; Preferably, the metaborate in step (1) comprises sodium metaborate.
3. The preparation method according to claim 1 or 2, characterized in that: The particle size D50 of the seed crystal in step (1) is 3-4.5 μm; Preferably, in the zirconium-doped mixed metal salt solution of step (1), the concentration of zirconium ions is 20-60 mmol / L; Preferably, in the zirconium-doped mixed metal salt solution of step (1), the molar ratio of nickel ions, cobalt ions and manganese ions is (0.9-0.98):(0.1-0.6):(0.1-0.2).
4. The preparation method according to any one of claims 1 to 3, characterized in that Step (1) The first base solution includes a complexing agent, a metaborate and a hydroxide; Preferably, in step (1), the pH of the first base solution is 11-12, the concentration of the complexing agent in the first base solution is 0.12-0.15 mol / L, the concentration of the hydroxide is 0.3-0.38 mol / L, and the concentration of the metaborate is 0.2-0.21 mol / L; Preferably, during the first coprecipitation reaction in step (1), the pH is 11-11.5 and the concentration of the complexing agent is 0.1-0.15 mol / L; Preferably, during the first coprecipitation reaction in step (1), the concentration of hydroxide is 1.8-2 mol / L, and the concentration of metaborate is 1-1.4 mol / L.
5. The preparation method according to any one of claims 1 to 4, characterized in that: Step (2) During the second coprecipitation reaction, the concentration of the metaborate solution is 4-8 mol / L; Preferably, during the second coprecipitation reaction in step (2), the pH is 7.5-9 and the concentration of the complexing agent is 0.2-0.25 mol / L.
6. The preparation method according to any one of claims 1 to 5, characterized in that: Step (2) the second base liquid comprises a complexing agent and a metaborate; Preferably, in step (2), the pH of the second base solution is 8-10, the concentration of the complexing agent is 0.2-0.3 mol / L, and the concentration of the metaborate is 6-8 mol / L.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The particle size D50 of the zirconium-doped high-nickel ternary precursor material in step (2) is 9-13 μm; Preferably, the PDI of the zirconium-doped high-nickel ternary precursor material in step (2) is 0.29-0.4; Preferably, the tap density of the zirconium-doped high-nickel ternary precursor material in step (2) is 1.98-2.1 g / cm 3 , with a specific surface area of 14.8-18m 2 / g.
8. A zirconium-doped high-nickel ternary precursor material, characterized in that: The zirconium-doped high-nickel ternary precursor material is prepared by the preparation method according to any one of claims 1 to 7.
9. A high-nickel ternary positive electrode material, characterized in that: The high-nickel ternary positive electrode material is obtained by mixing and sintering a lithium source and the zirconium-doped high-nickel ternary precursor material as claimed in claim 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the high-nickel ternary positive electrode material as claimed in claim 9.
Citation Information
Patent Citations
Method for preparing narrow-distribution precursor in grading manner
CN111717940A